The role of the conflictogenity in the process of cultural integration - Shakirov, S.Ye.; Amangeldiyev, A.A.; Mustafina, T.V. (Karaganda University named after academician E.A.Buketov, 2023)
Integration processes, often seen as a way to cooperation and common prosperity, turn out to be complex studies that hide many subtle aspects within them that can either promote unity or lead to divisions. In this article, the authors consider the role of the conflict factor in integration processes. Conflictogenity means the tendency of certain factors to cause social conflicts and plays a significant role in determining the success or failure of integration efforts. Our article focuses on one of the important aspects of conflict, namely the process of cultural integration, which can hinder the smooth process of integration. The importance of cultural integration as the main strategy of cultural policy in Kazakhstan is emphasized in our article. This requires a scientific and methodological approach based on cultural principles. The research on cultural integration in Kazakhstan, its efforts to promote cooperation, preserve cultural heritage and support intercultural communication, should be a fundamental component of the integration process. Despite the fact that conflictogenity can cause problems, special attention is paid to strategies for their prevention and cooperation in our article. We analyze mechanisms that can overcome and prevent conflicts, ways to develop dialogue and mutual understanding. We also emphasize the importance of inclusive decision-making mechanisms and participatory measures that help defuse conflictogenity. Our considerations include the study of cultural dialogue, exchange of experiences and the protection of human rights as ways to strengthen intercultural harmony.
Мәдени интеграция үдерісіндегі конфликтогендік фактордың рөлі
Роль фактора конфликтогенности в процессе культурной интеграции
Keywords: integration; conflictogenicity; cultural integration; social conflicts; conflict prevention; mediation